Sally modules and reduction numbers of ideals - Ghezzi, L.; Goto, S.; Hong, J.; Vasconcelos, W. V. (Nagoya Mathematical Journal, 2017)
We study the relationship between the reduction number of a primary ideal of a local ring relative to one of its minimal reductions and the multiplicity of the corresponding Sally module. This paper is focused on three goals: (i) to develop a change of rings technique for the Sally module of an ideal to allow extension of results from Cohen–Macaulay rings to more general rings; (ii) to use the fiber of the Sally modules of almost complete intersection ideals to connect its structure to the Cohen–Macaulayness of the special fiber ring; (iii) to extend some of the results of (i) to two-dimensional Buchsbaum rings. Along the way, we provide an explicit realization of the S2S_{2} -fication of arbitrary Buchsbaum rings.
3 citations (Crossref) [2023-10-31]
Keywords: 13D40; 13H15; Primary 13H10; Secondary 13A30; dept.mat